LncRNA MAGI2-AS3 Overexpression Sensitizes Esophageal Cancer Cells to Irradiation Through Down-Regulation of HOXB7 via EZH2 - Cheng, Wenfang; Shi, Xiuling; Lin, Mingqiang; Yao, Qiwei; Ma, Jiayu; Li, Jiancheng (Frontiers in Cell and Developmental Biology, 2020)
Background: Accumulating evidence has suggested that aberrant expression of long noncoding RNAs (lncRNAs) may contribute to cancer progression in association with radioresistance. The current study aimed to identify the potential role of lncRNA MAGI2-AS3 and the underlying mechanism in its regulation of the radio-sensitivity of esophageal cancer cells. Methods and Results: Initially, we detected high expression of HOXB7 from microarray-based gene expression profiling of esophageal cancer. Then, we identified the interactions among MAGI2-AS3, HOXB7 and EZH2 by dual-luciferase reporter gene assay, RNA pull-down assay, RIP assay and ChIP assay. HOXB7 was highly-expressed, while MAGI2-AS3 was poorly-expressed in esophageal cancer tissues and cells. The effect of MAGI2-AS3 and HOXB7 on esophageal cancer cell proliferation and apoptosis as well as tumorigenicity of radioresistant cells was examined by gain- and loss-of-function experiments. Interestingly, MAGI2-AS3 down-regulated HOXB7 through interaction with EZH2, which promoted cell apoptosis and inhibited proliferation and radio-resistance. Besides, down-regulation of MAGI2-AS3 exerted a promoting effect on these malignant phenotypes. Conclusion: Taken together, our results reveal the potential role of MAGI2-AS3 over-expression in controlling esophageal cancer resistance to radiotherapy by down-regulating HOXB7, this providing a candidate biomarker for resistance to radiotherapy.